Rationing rules and stable coalition structures - Oihane Gallo; Elena I\~narra García (Theoretical Economics, 2018)
This paper introduces a model of coalition formation with claims. It assumes that agents have claims over the outputs they could produce by forming coalitions. Outputs, insufficient to meet the claims and are rationed by a rule whose proposals of division induce each agent to rank the coalitions in which she can participate. As a result, a hedonic game of coalition formation emerges. Using resource monotonicity and consistency, we characterize the continuous rationing rules that induce hedonic games that admit core-stability.
Keywords: C71; D63; D74; 330; Coalition formation; hedonic games; core-stability; rationing rules